Porous coordination cage materials, methods of making and applications thereof

CN122628347BActive Publication Date: 2026-10-13BEIFANG UNIV OF NATITIES
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202611138829.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-07-29
Publication Date
2026-10-13
Estimated Expiration
2046-07-29

AI Technical Summary

Technical Problem

[0005]然而,MOFs作为三维无限延伸的框架材料,其不溶或难溶的特性严重限制了其在溶液加工场景中的应用

Benefits of technology

[0031]本发明提供多孔配位笼材料,所述多孔配位笼材料以三核Cp3Zr3(μ3-O)(μ2-OH)3型次级构筑单元为顶点、均苯四甲酸部分脱质子羧基为桥连臂,形成笼径可调、窗口尺寸3-6Å的离散超分子空腔结构,所述离散超分子空腔结构存在至少1个未配位的游离羧基,以形成能够与氢键结合的HOF材料,所述多孔配位笼材料经活化后可暴露丰富的Zr(IV)位点与限域孔道,对小分子和气体表现出选择性吸附能力,可用于H2、CH4、CO2、C2烃等气体的吸附储存与C1/C2、CO2/N2、CO2/CH4分离,并且具有优异的水解/热稳定性,适合工业气体分离。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122628347B_ABST
    Figure CN122628347B_ABST
Patent Text Reader

Abstract

The application provides a kind of porous coordination cage material and its preparation method and application, belong to gas adsorption technical field, the porous coordination cage material with the secondary building unit of three-core Cp3Zr3 (μ3-O) (μ2-OH) 3 type as vertex, partial deprotonation carboxyl of benzene-1, 4-tetracarboxylic acid is bridged arm, form the discrete supramolecular cavity structure of adjustable cage diameter, window size 3-6 angstrom, the discrete supramolecular cavity structure exists at least 1 uncoordinated free carboxyl group, to form the HOF material capable of being combined with hydrogen bond, the porous coordination cage material can expose abundant Zr (IV) site and limited domain channel after activation, show selective adsorption capacity to small molecule and gas, can be used for H2, CH4, CO2, C2 hydrocarbon etc. Gas adsorption storage and C1 / C2, CO2 / N2, CO2 / CH4 separation, and have excellent hydrolysis / thermal stability, suitable for industrial gas separation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of gas adsorption technology, specifically to a porous coordination cage material, its preparation method, and its application. Background Technology

[0002] Gas separation is one of the core technological requirements in the energy and environment sectors. In recent years, CO2 capture, utilization, and storage (CCUS) technology has received widespread attention. Meanwhile, the efficient separation and purification of C1 / C2 light hydrocarbons (such as CH4, C2H4, C2H6, and C2H2) in the petrochemical industry is also a key step in reducing energy consumption and increasing product added value. However, traditional separation methods face prominent problems such as poor selectivity and high energy consumption.

[0003] Currently, the mainstream separation processes in industry mainly include cryogenic distillation and amine absorption. Cryogenic distillation achieves separation by utilizing the differences in boiling points of the components, but it requires operation under low temperature and high pressure conditions, resulting in large equipment investment and extremely high energy consumption. Although amine absorption can selectively capture acidic gases such as CO2, the amine regeneration process consumes a huge amount of heat and suffers from problems such as equipment corrosion and amine degradation. Therefore, developing new separation materials and technologies with low energy consumption and high efficiency has become a common research direction for academia and industry.

[0004] Porous solid adsorbents are considered important candidate materials for replacing traditional processes due to their advantages such as mild operating conditions and low regeneration energy consumption. Among them, zeolite molecular sieves have been widely used in gas adsorption and separation due to their regular microporous structure and good thermal stability; activated carbon has attracted much attention due to its high specific surface area and low cost. Metal-organic frameworks (MOFs), as a class of crystalline porous materials constructed by coordination bonds between metal nodes and organic ligands, have shown great potential in the field of gas adsorption and separation in recent years due to their outstanding advantages such as strong structural designability, adjustable pore size, and functional modification. In particular, the UiO-66 series Zr-MOFs with Zr6 clusters as nodes have excellent thermal and chemical stability due to the high bond energy of the Zr-O coordination bonds, and have become one of the most extensively studied MOF systems in the field of gas separation.

[0005] However, the insoluble or poorly soluble nature of MOFs, as three-dimensional infinitely extended framework materials, severely limits their application in solution processing. For example, in the preparation of mixed-matrix membranes (MMMs), insoluble fillers are difficult to disperse uniformly in the polymer matrix, easily leading to interfacial defects and a decline in membrane separation performance. This bottleneck has prompted researchers to turn their attention to zero-dimensional (0D) porous materials with discrete molecular structures.

[0006] Porous coordination cages (PCCs), also known as metal-organic cages (MOCs) or metal-organic polyhedra (MOPs), are discrete molecular entities formed by the coordination self-assembly of metal ions / clusters and organic ligands. Unlike the infinitely extended network of MOFs, MOCs have definite molecular dimensions and independent cavity structures. This discreteness endows MOCs with unique solubility and processability—they are soluble in organic solvents and uniformly dispersed in polymer matrices, effectively overcoming the interfacial compatibility problems of insoluble fillers such as MOFs in membrane preparation. Furthermore, when MOCs are solid materials, the stacking patterns between their molecular cages are diverse, forming various supramolecular frameworks and allowing for post-modification to impart new functions. These characteristics make MOCs promising for applications in gas adsorption and separation, catalysis, biomedicine, and water treatment.

[0007] Among the many metal-organic cages (MOCs), zirconium-based metal-organic cages (Zr-MOCs) have attracted particular attention due to their outstanding stability and high solubility. The high stability of Zr-MOCs stems from the high bond energy of the Zr-O coordination bond, giving them both good thermal and hydrothermal stability.

[0008] In the prior art, for example, Chinese invention application number 202510268531.7 discloses a gas separation membrane based on a metal-organic cage, its preparation method, and its application. Specifically, it includes preparing a membrane containing a metal salt (zirconium dichloroethylene), organic ligands (2,5-dihydroxyterephthalic acid, 2,3-dihydroxyterephthalic acid, 2,5-bis(trifluoromethyl)terephthalic acid, 2,5-dihydroxyphenyl phthalic acid, and 1,1'-biphenyl-4,4'-dicarboxylic acid). A solution of an acid, 2,3,5,6-tetrafluoroterephthalic acid, 4,5,9,10-tetrahydropyrene-2,7-dicarboxylic acid, etc., and an organic solvent is reacted at a temperature range of 50~200℃ for 2~160h to obtain a metal-organic cage material. This invention uses a solvothermal method to cause metal ions to undergo coordination reactions with polycarboxylic acid ligands or imidazole ligands to form a metal-organic cage structure, so that the metal-organic cage material has an adjustable pore structure and abundant reactive functional groups.

[0009] Based on the above, it is necessary to provide a new molecular cage for application in gas separation and adsorption. Summary of the Invention

[0010] In view of this, the present invention provides a novel porous coordination cage material for application in gas separation and adsorption.

[0011] It is also necessary to provide a method for preparing porous coordination cage materials.

[0012] It is also necessary to provide an application of porous coordination cage material in gas adsorption and separation.

[0013] The technical solution adopted by this invention to solve its technical problem is:

[0014] A porous coordination cage material, wherein the porous coordination cage material uses trinuclear Cp3Zr3(μ3-O)(μ2-OH)3 type secondary building units as vertices and partially deprotonated carboxyl groups of pyromellitic tetracarboxylic acid as bridging arms to form a discrete supramolecular cavity structure with adjustable cage diameter and window size of 3-6 Å. The discrete supramolecular cavity structure has at least one uncoordinated free carboxyl group to form a HOF material that can bind with hydrogen bonds.

[0015] Preferably, the diameter of the discrete supramolecular cavity structure is 0.6–2.3 nm.

[0016] Preferably, in the trinuclear Cp3Zr3(μ3-O)(μ2-OH)3 type secondary building block, Zr is in the +4 valence state and Cp is in the η valence state. 5 -C5H5, with Zr-O bond length of 2.05-2.25 Å, the discrete supramolecular cavity structure retains Lewis acidic Zr sites and π-aromatic ring confinement surfaces on its surface, which together constitute gas recognition and polarization interaction sites.

[0017] A method for preparing the porous coordination cage material as described above includes the following steps:

[0018] Zirconium dichlorocerocene and pyromellitic acid were dissolved in a solvent and water and then self-assembled to obtain a solid.

[0019] Preferably, the molar ratio of the zirconium dichlorocerocene to the pyromellitic acid is (2-12):1.

[0020] Preferably, the solvent is one or more of DMF, DEF, NMP, MeOH, EtOH, CH3CN, acetone, dichloromethane, and toluene, and the water content of the solvent is in the range of 50-2000 ppm.

[0021] Preferably, the self-assembly can be driven by a solvent method, a layered diffusion method, or a gas-phase diffusion method. In the solvent method, the zirconium source solution is mixed with a pyromellitic acid solution, water is added, and the mixture is reacted at 25–100°C for 12–72 h to carry out self-assembly, and then the mixture is allowed to cool naturally to obtain crystals.

[0022] A layered diffusion method was used, in which zirconium source solution was mixed with pyromellitic acid solution and water was added. Methanol, acetonitrile, DMF, DEF, anhydrous diethyl ether, or n-hexane were used as the upper solvent for slow diffusion. The mixture was allowed to stand at room temperature or -60°C for 2 to 14 days to undergo self-assembly and obtain a solid.

[0023] The zirconium source solution was mixed with a pyromellitic acid solution using a gas-phase diffusion method, and water was added. Then, hexane or anhydrous diethyl ether was added for diffusion, and the mixture was self-assembled at room temperature or low temperature to obtain a solid.

[0024] As described above, porous coordination cage materials are used in gas adsorption and separation. By molding these materials into shaped bodies, the following gas adsorption or separation can be performed:

[0025] CO2 capture: selective adsorption of CO2 from CO2 / N2, CO2 / CH4, or CO2 / C2H2 / N2 mixtures;

[0026] C1 / C2 separation: kinetic sieving or affinity separation of CH4 / C2H6 / C2H4;

[0027] Light gas storage: adsorption and separation of H2 and CH4 at low temperature and medium pressure;

[0028] Confined adsorption of rare gases / volatile organic compounds.

[0029] Preferably, before gas adsorption or separation, the porous coordination cage material needs to be activated. Specifically, the porous coordination cage material is washed with chloroform to remove unreacted reagents; then activated in a dynamic vacuum or inert gas flow to obtain activated porous coordination cage material.

[0030] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0031] This invention provides a porous coordination cage material. The porous coordination cage material uses a trinuclear Cp3Zr3(μ3-O)(μ2-OH)3 type secondary building unit as the apex and partially deprotonated carboxyl groups of pyromellitic tetracarboxylic acid as bridging arms to form a discrete supramolecular cavity structure with an adjustable cage diameter and a window size of 3-6 Å. The discrete supramolecular cavity structure contains at least one uncoordinated free carboxyl group to form a HOF material that can bind with hydrogen bonds. After activation, the porous coordination cage material can expose abundant Zr(IV) sites and confined channels, exhibiting selective adsorption capacity for small molecules and gases. It can be used for the adsorption and storage of gases such as H2, CH4, CO2, and C2 hydrocarbons, as well as the separation of C1 / C2, CO2 / N2, and CO2 / CH4. It also has excellent hydrolytic / thermal stability, making it suitable for industrial gas separation.

[0032] Based on the Lewis acid-base theory, a strong coordination relationship exists between metallic zirconium (Zr) and its carboxyl groups. Zirconia dichlorodichlorohydrogenase hydrolysis yields claw-like trinuclear zirconium-ceramic clusters. Therefore, zircononia dichlorodi ... 4+ Type SBU; the four -COOH groups of pyromellitic acid can be deprotonated in batches / sections, with µ2-κ 1 κ 1 or µ2-κ 2 The mode bridges two adjacent Cp3Zr3 clusters; by controlling n(Cp2ZrCl2):n(H4PMTC), pH / base equivalent, temperature and solvent polarity, the system is kept in the "finite connection" stage → oligomerization → closed cage (rather than infinite extension); after activation, guest protons / solvents / counterions are removed to obtain permanent pores (BET>0). Attached Figure Description

[0033] Figure 1 The XRD patterns of the synthesized materials in Examples 1, 3, and 4 are shown.

[0034] Figure 2 The infrared absorption spectrum was obtained by the KBr pellet method in Example 1.

[0035] Figure 3 This is the SEM image of Example 1.

[0036] Figure 4 This is the EDS data for Example 1.

[0037] Figure 5 The N2-77K adsorption-desorption curves are from Example 1.

[0038] Figure 6 This is a pore size distribution diagram for Example 1.

[0039] Figure 7 The adsorption-desorption curves of single-component gases C2H2 and N2 under 285K and 298K conditions are shown.

[0040] Figure 8 The fitted curves of C2H2 and N2 (1:99) IAST under 285K conditions.

[0041] Figure 9 The fitted curves of C2H2 and N2 (1:99) IAST under 298K conditions.

[0042] Figure 10 The fitted curves of C2H2 and N2 (10:90) IAST under 285K conditions.

[0043] Figure 11 The fitted curves of C2H2 and N2 (10:90) IAST under 298K conditions.

[0044] Figure 12 The fitted curves of C2H2 and N2 (20:80) IAST under 285K conditions.

[0045] Figure 13 The fitted curves of C2H2 and N2 (20:80) IAST under 298K conditions.

[0046] Figure 14 The fitted curves of C2H2 and N2 (50:50) IAST under 285K conditions.

[0047] Figure 15 The fitted curves of C2H2 and N2 (50:50) IAST under 298K conditions.

[0048] Figure 16 The selective adsorption separation curves for the C2H2 and N2 mixed components are shown.

[0049] Figure 17 The curves show the selectivity as a function of C2H2 components under conditions of 285K and 298K.

[0050] Figure 18 This is the Qst curve for Example 1. Detailed Implementation

[0051] To facilitate understanding of this application, a more comprehensive description will be provided below with reference to the accompanying drawings. Preferred embodiments of this application are also given. However, this application can be implemented in many different forms and is not limited to the embodiments described herein. Rather, these embodiments are provided to enable a more thorough and complete understanding of the disclosure of this application.

[0052] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs. The terminology used herein in the specification of this application is for the purpose of describing particular embodiments only and is not intended to be limiting of the application. The term "and / or" as used herein includes any and all combinations of one or more of the associated listed items.

[0053] A porous coordination cage material, wherein the porous coordination cage material uses trinuclear Cp3Zr3(μ3-O)(μ2-OH)3 type secondary building units as vertices and partially deprotonated carboxyl groups of pyromellitic tetracarboxylic acid as bridging arms to form a discrete supramolecular cavity structure with adjustable cage diameter and window size of 3-6 Å. The discrete supramolecular cavity structure has at least one uncoordinated free carboxyl group to form a HOF material that can bind with hydrogen bonds.

[0054] Specifically, zirconium dichlorocerocene (Cp2ZrCl2) undergoes controlled hydrolysis-condensation in the presence of water to form the trinuclear zirconium-oxygen cluster secondary building unit Cp3Zr3O(OH). 3+ Then react with pyromellitic acid (PMTC) 4- or partially deprotonated PMTC-H n (4-n)- The carboxylate groups are coordinated and linked to form discrete molecular-level porous coordination cages (PCC).

[0055] Furthermore, the diameter of the discrete supramolecular cavity structure is 0.6–2.3 nm.

[0056] Furthermore, in the trinuclear Cp3Zr3(μ3-O)(μ2-OH)3 type secondary building block, Zr is in the +4 valence state and Cp is in the η valence state. 5 -C5H5, with Zr-O bond length of 2.05-2.25 Å, the discrete supramolecular cavity structure retains Lewis acidic Zr sites and π-aromatic ring confinement surfaces on its surface, which together constitute gas recognition and polarization interaction sites.

[0057] A method for preparing the porous coordination cage material as described above includes the following steps:

[0058] Zirconium dichlorocerocene and pyromellitic acid were dissolved in a solvent and water and then self-assembled to obtain a solid.

[0059] Furthermore, the molar ratio of the zirconium dichlorocerocene to the pyromellitic acid is (2-12):1.

[0060] Furthermore, the solvent is one or more of DMF, DEF, NMP, MeOH, EtOH, CH3CN, acetone, dichloromethane, and toluene, and the water content of the solvent is in the range of 50-2000 ppm.

[0061] Furthermore, the self-assembly can be driven by solvent method, layer diffusion method, or gas phase diffusion method; in the solvent method, the zirconium source solution is mixed with the pyromellitic acid solution, water is added, and the reaction is carried out at 25-100°C for 12-72 hours to carry out self-assembly, and then the crystal is obtained by natural cooling.

[0062] A layered diffusion method was used, in which zirconium source solution was mixed with pyromellitic acid solution and water was added. Methanol, acetonitrile, DMF, DEF, anhydrous diethyl ether, or n-hexane were used as the upper solvent for slow diffusion. The mixture was allowed to stand at room temperature or -60°C for 2 to 14 days to undergo self-assembly and obtain a solid.

[0063] The zirconium source solution was mixed with a pyromellitic acid solution using a gas-phase diffusion method, and water was added. Then, hexane or anhydrous diethyl ether was added for diffusion, and the mixture was self-assembled at room temperature or low temperature to obtain a solid.

[0064] As described above, porous coordination cage materials are used in gas adsorption and separation. By molding these materials into shaped bodies, the following gas adsorption or separation can be performed:

[0065] CO2 capture: selective adsorption of CO2 from CO2 / N2, CO2 / CH4, or CO2 / C2H2 / N2 mixtures;

[0066] C1 / C2 separation: kinetic sieving or affinity separation of CH4 / C2H6 / C2H4;

[0067] Light gas storage: adsorption and separation of H2 and CH4 at low temperature and medium pressure;

[0068] Confined adsorption of rare gases / volatile organic compounds.

[0069] Furthermore, before gas adsorption or separation, the porous coordination cage material needs to be activated. Specifically, the porous coordination cage material is washed with chloroform to remove unreacted reagents; then activated in a dynamic vacuum or inert gas flow to obtain activated porous coordination cage material.

[0070] Furthermore, the operating temperature for gas adsorption or separation is 0℃~200℃, and the operating pressure is 0-1 bar.

[0071] The present invention will now be described through the following embodiments and comparative examples.

[0072] Example 1: Preparation by solvothermal method (main example)

[0073] Operating steps:

[0074] Reagents: Cp₂ZrCl₂: 17.5 mg (0.06 mmol); H₄PMTC: 7.6 mg (0.03 mmol); DMF: 0.5 ml; Deionized water: 5 drops;

[0075] After weighing the reagent, dissolve it in DMF and a trace amount of deionized water, accelerate the dissolution with sonication, and then heat it in a 60℃ constant temperature oven for 12 hours. After naturally cooling to room temperature, centrifuge to obtain white powder crystals. Wash three times with DMF solvent (3×7ml) to remove unreacted ligands and metal sources. Then wash three times with chloroform, soaking for 24 hours during the third wash, and centrifuge again to obtain white powder crystals. Then activate under vacuum at 60℃-100℃ for 12-24 hours.

[0076] Example 2:

[0077] Operating steps:

[0078] Reagents: Cp₂ZrCl₂: 350 mg (1.2 mmol); H₄PMTC: 153 mg (0.6 mmol); DMF: 15 ml; Deionized water: 3 ml;

[0079] After weighing the reagent, dissolve it in DMF and a trace amount of deionized water, accelerate the dissolution with sonication, and then heat it in a 60℃ constant temperature oven for 12 hours. After naturally cooling to room temperature, centrifuge to obtain white powder crystals. Wash three times with DMF solvent (3×7ml) to remove unreacted ligands and metal sources. Then wash three times with chloroform, soaking for 24 hours during the third wash, and centrifuge again to obtain white powder crystals. Then activate under vacuum at 60℃-100℃ for 12-24 hours.

[0080] Example 3:

[0081] Operating steps:

[0082] Reagents: Cp₂ZrCl₂: 350 mg (1.2 mmol); H₄PMTC: 153 mg (0.6 mmol); DMF: 15 ml; Deionized water: 3 ml;

[0083] After weighing the reagent, dissolve it in DMF and a trace amount of deionized water, accelerate the dissolution with sonication, and then heat it in a 45℃ constant temperature oven for 12 hours. After naturally cooling to room temperature, centrifuge to obtain white powder crystals. Wash three times with DMF solvent (3×7ml) to remove unreacted ligands and metal sources. Then wash three times with chloroform, soaking for 24 hours during the third wash, and centrifuge again to obtain white powder crystals. Then activate under vacuum at 60℃-100℃ for 12-24 hours.

[0084] Example 4:

[0085] Operating steps:

[0086] Reagents: Cp₂ZrCl₂: 350 mg (1.2 mmol); H₄PMTC: 153 mg (0.6 mmol); DMF: 15 ml; Deionized water: 3 ml;

[0087] After weighing the reagent, dissolve it in DMF and a trace amount of deionized water, accelerate the dissolution with sonication, and then allow it to react naturally at room temperature (25℃) for 24 hours. Centrifuge to obtain white powder crystals. Wash three times with DMF solvent (3×7ml) to remove unreacted ligands and metal sources. Then wash three times with chloroform, soaking for 24 hours during the third wash, and centrifuge again to obtain white powder crystals. Then activate under vacuum at 60℃-100℃ for 12-24 hours.

[0088] Example 5: Layered diffusion method (for synthesizing single crystals)

[0089] Operating steps:

[0090] Reagents: Cp₂ZrCl₂: 17.5 mg (0.06 mmol); H₄PMTC: 7.6 mg (0.03 mmol); DMF: 0.5 ml; Deionized water: 5 drops;

[0091] After weighing the reagent, dissolve it in DMF and a trace amount of deionized water, accelerate the dissolution with sonication, and then add anhydrous diethyl ether along the wall of the reaction vessel. Then react slowly at room temperature or low temperature for 4-14 days.

[0092] Example 6: Vapor-phase diffusion method (for synthesizing single crystals)

[0093] Operating steps:

[0094] Reagents: Cp₂ZrCl₂: 17.5 mg (0.06 mmol); H₄PMTC: 7.6 mg (0.03 mmol); DMF: 0.5 ml; Deionized water: 5 drops;

[0095] After weighing the reagent, dissolve it in DMF and a trace amount of deionized water. Sonicate the solution until dissolved, then add the mixture to a 2ml glass bottle without sealing it. Place the small glass bottle in the center of a larger glass bottle, and add n-hexane or anhydrous diethyl ether along the wall of the larger bottle. The solvent level in the larger bottle should not exceed two-thirds of the height of the small bottle. After sealing the larger bottle, place it in a dark, quiet place at room temperature for 4-12 days to react.

[0096] 1. Examples 1, 3, and 4 were subjected to XRD analysis. Specifically, data within the 5-45° range were measured at room temperature using a Rigaku SmartlabSE instrument at a scanning speed of 5° / min. Figure 1 As shown, the activation was measured after chloroform treatment in Example 1.

[0097] PXRD analysis confirmed that the synthesized sample exhibited excellent crystallinity and high phase purity. Furthermore, the material could be stably synthesized under various temperature conditions. Comparison of materials synthesized at different temperatures revealed distinct diffraction peaks at approximately 9.5°, 11°, and 13.6°, and fixed diffraction peaks at 5.5°, 12°, 19.2°, and 21.4°. Therefore, the peak positions and intensity ratios remained essentially unchanged across different temperature conditions, confirming that the same material was synthesized at room temperature, 45°C, and 60°C. Analysis of the activated XRD data showed that the peak positions and intensity ratios did not change after activation, indicating that the synthesized material maintained its crystal structure and crystallinity before and after activation.

[0098] 2. The infrared absorption spectrum of the product from Example 1 was measured using a Thermo Fisher Nicolet iS50 instrument via the KBr pellet method, as shown below. Figure 2 As shown.

[0099] Infrared spectral data analysis at 1700cm -1 The presence of a free carboxyl peak indicates that the molecular cage is a novel structure containing free carboxyl groups, rather than a MOF structure. The presence of free carboxyl groups in the molecular cage provides a good platform for subsequent catalysis, adsorption, and drug delivery.

[0100] 3. The product of Example 1 was measured using a Sigma 500 thermal field scanning electron microscope, with images taken at 5KV magnification at 2K and 7K. Figure 3 As shown.

[0101] SEM images show that the material has a hemispherical morphology with uniform size. This indicates that the synthesized material is a novel material with a unique morphological structure, completely different from previously reported zirconium-based metal-caged MOF materials such as capsules, rods, and cubic structures.

[0102] 4. Surface elemental distribution data of the material are obtained by performing surface scanning on the images seen by SEM, such as... Figure 4 As shown.

[0103] EDS data indicates that the material is mainly composed of elements such as zirconium, oxygen, carbon, and chlorine, which is consistent with the raw materials used.

[0104] 5. The BET data and intrinsic pore size data of the product from Example 1 were obtained by nitrogen adsorption-desorption at 77K using a BSD-660MG instrument. Figure 5 , Figure 6 As shown.

[0105] Depend on Figure 5 The BET value was calculated to be 992.2m using the Langmuir multi-point method. 3The material has a high specific surface area ( / g), which provides more adsorption sites for gas adsorption, thus improving adsorption and separation efficiency. Figure 6 It can be determined that the pore size of the material is around 0.6-2.3 nm, indicating that the material is a porous metal-organic coordination cage with micropore size.

[0106] 6. The single-component adsorption data of C2H2 and N2 at 285K and 298K, 0-1.0 bar, respectively, were measured using a BSD-660MG instrument via static volumetric method. The results are as follows. Figure 7 As shown.

[0107] Depend on Figure 7 It can be seen that at a pressure of 1 bar and a temperature of 285 K, the acetylene adsorption capacity is approximately 50 cm³. 3 / g, nitrogen adsorption capacity less than 5cm 3 / g, and the adsorption amount decreases with increasing temperature.

[0108] 7. The single-component adsorption data of acetylene (C2H2) and carbon dioxide (CO2) obtained from the product of Example 1 were fitted using a BSD-660MG instrument. The adsorption and separation performance of different components of C2H2 and CO2 was then fitted using the Langmuir-Freundlich model, and the results are as follows: Figure 8-15 As shown.

[0109] Depend on Figures 8-15 It can be seen that the fitted data were obtained with acetylene and nitrogen compositions of (1%:99%; 10%:90%; 20%:80%; 50%:50%). The adsorption behavior of acetylene and nitrogen conforms to the Langmuir-Freundlich model, indicating that the surface energy distribution of the material is asymmetric.

[0110] 8. Using a BSD-660MG instrument, single-component data for C2H2 and CO2 were measured at 285K and 298K temperatures and 0-1.0 bar pressures, respectively. Graphs were plotted on the C2H2 and CO2 data measured at 285K and 298K. Trace acetylene and selectivity data for a 1:1 mixture of acetylene and nitrogen were obtained, as shown below. Figure 16 As shown.

[0111] Depend on Figure 16 The selectivity data obtained from the adsorption separation of acetylene and nitrogen show that the selectivity is about 53 at 298 K, 1.0 bar, and the selectivity increases to about 90 as the proportion of nitrogen increases.

[0112] 9. Single-component data for C2H2 and CO2 were measured using a BSD-660MG instrument at temperatures of 285K and 298K and pressures of 0-1.0 bar. The selectivity of the material for C2H2 and CO2 at different temperatures with varying C2H2 content was obtained by fitting the Langmuir-Freundlich model. Figure 17 As shown.

[0113] pass Figure 17 This indicates that the material generally exhibits a decrease in selectivity for C2H2 and CO2 as the temperature increases. However, at the same temperature, as the C2H2 content increases, the selectivity at low temperatures first decreases and then increases with the increase of C2H2 content, while at high temperatures, the selectivity gradually decreases with the increase of C2H2 content.

[0114] 10. The single-component data of the product of Example 1 were measured by a BSD-660MG instrument at 285K and 298K under 0-1.0 bar conditions. The adsorption heat data of C2H2 and N2 were obtained by fitting the data measured at 285K and 298K respectively.

[0115] Depend on Figure 18 Qst data indicate that the material has an adsorption heat of approximately 20 kJ / mol for C2H2, which is a physical adsorption process, while the adsorption heat for nitrogen is approximately 12 kJ / mol.

[0116] The above-disclosed embodiments are merely preferred embodiments of the present invention and should not be construed as limiting the scope of the invention. Those skilled in the art will understand that implementing all or part of the above-described embodiments and making equivalent changes in accordance with the claims of the present invention are still within the scope of the invention.

Claims

1. A porous coordination cage material, characterized in that, The porous coordination cage material uses trinuclear Cp3Zr3(μ3-O)(μ2-OH)3 type secondary building units as vertices and partially deprotonated carboxyl groups of pyromellitic tetracarboxylic acid as bridging arms to form a discrete supramolecular cavity structure with adjustable cage diameter and window size of 3–6 Å. The discrete supramolecular cavity structure has at least one uncoordinated free carboxyl group to form a HOF material that can bond with hydrogen bonds.

2. The porous coordination cage material as described in claim 1, characterized in that, The diameter of the discrete supramolecular cavity structure is 0.6–2.3 nm.

3. The porous coordination cage material as described in claim 1, characterized in that, In the trinuclear Cp3Zr3(μ3-O)(μ2-OH)3 type secondary building block, Zr is in the +4 valence state, and Cp is in the η valence state. 5 -C5H5, with Zr-O bond length of 2.05-2.25 Å, the discrete supramolecular cavity structure retains Lewis acidic Zr sites and π-aromatic ring confinement surfaces on its surface, which together constitute gas recognition and polarization interaction sites.

4. A method for preparing the porous coordination cage material as described in claim 1, characterized in that, Includes the following steps: Zirconium dichlorocerocene and pyromellitic acid were dissolved in a solvent and water and then self-assembled to obtain a solid.

5. The method as described in claim 4, characterized in that, The molar ratio of the dichlorozirconia to the pyromellitic acid is (2-12):

1.

6. The method as described in claim 4, characterized in that, The solvent is one or more of DMF, DEF, NMP, MeOH, EtOH, CH3CN, acetone, dichloromethane, and toluene, and the water content of the solvent is in the range of 50-2000 ppm.

7. The method as described in claim 4, characterized in that, The self-assembly can be driven by solvent method, layered diffusion method, or gas phase diffusion method. The zirconium source solution was mixed with pyromellitic acid solution and water was added. The mixture was reacted at 25–100 °C for 12–72 h to carry out self-assembly, and then naturally cooled to obtain crystals. A layered diffusion method was used, in which zirconium source solution was mixed with pyromellitic acid solution and water was added. Methanol, acetonitrile, DMF, DEF, anhydrous diethyl ether, or n-hexane were used as the upper solvent for slow diffusion. The mixture was allowed to stand at room temperature or -60°C for 2 to 14 days to undergo self-assembly and obtain a solid. The zirconium source solution was mixed with a pyromellitic acid solution using a gas-phase diffusion method, and water was added. Then, hexane or anhydrous diethyl ether was added for diffusion, and the mixture was self-assembled at room temperature or low temperature to obtain a solid.

8. The application of the porous coordination cage material as described in claim 1 in gas adsorption and separation, characterized in that: By molding porous coordination cage materials into shaped bodies, the following gas adsorption or separation can be achieved: CO2 capture: selective adsorption of CO2 from CO2 / N2, CO2 / CH4, or CO2 / C2H2 / N2 mixtures; C1 / C2 separation: kinetic sieving or affinity separation of CH4 / C2H6 / C2H4; Light gas storage: adsorption and separation of H2 and CH4 at low temperature and medium pressure; Confined adsorption of rare gases / volatile organic compounds.

9. The application as described in claim 8, characterized in that: Before gas adsorption or separation, the porous coordination cage material needs to be activated. Specifically, the porous coordination cage material is washed with chloroform to remove unreacted reagents; then activated in a dynamic vacuum or inert gas flow to obtain activated porous coordination cage material.

Citation Information

Patent Citations

  • Gas separation membrane based on metal organic cage as well as preparation method and application of gas separation membrane

    CN119857380A

  • Self-assembly tetrahedral supramolecular cage based on triptycene coordination, preparation method and application

    CN115850161A

  • Dental implant with antibacterial / antimicrobial property having metal-organic framework (MOF) structure and production method thereof

    US20220241055A1